Monitoring and evaluation of agricultural subsidy programs - Takeshima, Hiroyuki; Lee, Hak Lim (International Food Policy Research Institute, 2012)
Monitoring and evaluation (M&E) is a critical aspect of agricultural input subsidy policy and programs. The M&E of subsidies should not only focus on implementation issues such as targeting effectiveness, but also on the key development outcomes sought in establishing a subsidy program. Only by rigorously evaluating the impact of a program of subsidies can the value obtained for the public resources expended on the program be determined.